Molecular Hyperthermia: Spatiotemporal Protein Unfolding and Inactivation by Nanosecond Plasmonic Heating. Issue 36 (11th July 2017) - Kang, Peiyuan; Chen, Zhuo; Nielsen, Steven O.; Hoyt, Kenneth; D'Arcy, Sheena; Gassensmith, Jeremiah J.; Qin, Zhenpeng
Abstract : Spatiotemporal control of protein structure and activity in biological systems has important and broad implications in biomedical sciences as evidenced by recent advances in optogenetic approaches. Here, this study demonstrates that nanosecond pulsed laser heating of gold nanoparticles (GNP) leads to an ultrahigh and ultrashort temperature increase, coined as "molecular hyperthermia", which causes selective unfolding and inactivation of proteins adjacent to the GNP. Protein inactivation is highly dependent on both laser pulse energy and GNP size, and has a well‐defined impact zone in the nanometer scale. It is anticipated that the fine control over protein structure and function enabled by this discovery will be highly enabling within a number of arenas, from probing the biophysics of protein folding/unfolding to the nanoscopic manipulation of biological systems via an optical trigger, to developing novel therapeutics for disease treatment without genetic modification. Abstract : Nanosecond plasmonic heating of gold nanoparticles creates an ultrahigh and ultrashort temperature increase, leading to selective inactivation and unfolding of proteins adjacent to the nanoparticle.